Forest plantations and its extension towards urban areas in metropolitan Valparaiso and associations with the increase of wildfires - Ruiz, Vannia; Munizaga, Juan; Salazar Burrows, Alejandro (Investigaciones Geográficas, 2017)
Since the 70s in central Chile, the expansion of forest plantations has been one of the main causes of landscape modification, being influenced by changes in land cover. Considering the national context of the forest fires that occurred during the summer of 2017, there is a generalized opinion that the occurrence of these events is related to the proximity and approach of the plantations to urban areas, especially in the Valparaíso Metropolitan Area (AMV). From this perspective, the decrease in the distance between the expansion of forest plantations and the expansion of urban land in the AMV was analyzed using a supervised classification of Landsat images for the years 1989 and 2015. Additionally, an analysis is made of the degree of severity of fires and landscape metrics are calculated through the FRAGSTATS program. The main results show an increase in area for forest plantations for the year 2015, doubling its size compared to 1989. From the metrics studied a greater heterogeneity was observed in the landscape. With regard to the severity index, a greater degree is observed in forest plantations with respect to other coverings such as agriculture or shurblands.